Implementation Of The Polya Problem Solving Approach In Mathematics Learning Through Group Investigation Strategy Based On Strategic Competence For Grade VII OF SMP N 1 Surakarta - Astuti, Aprilina Pramudi; , Dra. Nining Setyaningsih, M.Si (2013)
This research paper aims to analyze (1) the difference effect between Polya problem solving approach through Group Investigation strategy and conventional learning approach to student's mathematics achievement on the set material, (2) the difference effect of student's strategic competence to student's mathematics achievement on the set material, (3) the interaction between learning approaches and student's strategic competence to student's mathematics achievement on the set material. Population of the research is all of students in grade VII of SMP N 1 Surakarta consist of 8 classes. The research sample was taken two classes, i.e. grade VIIF consist of 24 students be experiment class using Polya problem solving approach through Group Investigation strategy and grade VIIE consist of 24 students be control class using conventional learning approach. Type of research is experimental research with methods of collecting data using test, questionnaire and documentation. Prerequisites test this research using normality test and homogeneity test. In this research using analysis of variance two-ways. The result of hyphotesis testing using a=5% it show that (1) F obs = 0,045 < F table = 4,072 so H0 is accepted it means there is no difference effect of learning approach to student's mathematics achievement on the set material, (2) F obs = 5,671> F table = 3,222 so H0 is rejected it means there is difference effect of student's strategic competence to student's mathematics achievement on the set mateial, (3) F obs = 0,288 < F table = 3,222 so H0 is accepted it means there is no interaction between learning approaches and student's strategic competence to student's mathematics achievement on the set material.